PENGABDIAN MASYARAKAT MELALUI OPTIMALISASI DESAIN MESIN PENGAYAK LIMBAH ORGANIK PADA TPS3R DESA CARANGREJO: Indonesia - Mualifi Usman; Ahmad Asrori Ainur Robby; Ertansia Pranigara Anugrah (ABIDUMASY, 2025)
Carangrejo Village, a participant in the Desa Berseri (Sparkling Village) and Kampung Berseri Astra (Astra's Sparkling Village) programs, is active in waste management through its TPS3R (Reduce, Reuse, Recycle Waste Management Site). A key obstacle in the composting process is the suboptimal performance of the screening machine, which causes slow drum rotation, noisy operation due to friction, and low production capacity (8-10 kg/day). Community Service to modify and optimize the organic waste screening machine to improve process efficiency. The method used is design engineering through literature study and direct field observation. The research resulted in a modification design that involves adding a rail to the lip of the drum's input hole. This modification successfully reduced direct friction between the drum and the bearing, resulting in smoother and faster drum rotation. The implications of this optimization include increased production capacity, shorter operational time, reduced vibration and noise, and prevention of machine overheating. Thus, this modification can support Carangrejo Village's organic waste management program to become more efficient and sustainable.